Análises e discussões sobre o japonês como língua de herança no contexto imigratório brasileiro - Nocente, Mateus Aoki [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
O presente trabalho tem como objetivo analisar o papel do japonês como língua de herança no contexto da imigração japonesa para o Brasil. Por meio de uma ampla revisão bibliográfica, o trabalho se empenha em discorrer sobre a história da imigração japonesa atrelada à preservação do idioma japonês entre os filhos de imigrantes. Com a vinda dos primeiros imigrantes japoneses para o Brasil, no início do século XX, a língua japonesa passou a ser transmitida aos filhos de imigrantes como uma herança cultural. Divididos entre um contexto familiar e uma sociedade com línguas distintas, os filhos e netos de imigrantes japoneses tiveram um contato heterogêneo com o idioma japonês resultando em diferentes vivências a respeito de ser filho de um migrante. Para além dos traços identitários dos indivíduos, percebe-se um protagonismo da língua japonesa na fundação de associações culturais que serviram como locais de reterritorialização do espaço brasileiro pelos imigrantes japoneses. Essas dinâmicas inerentes ao movimento migratório contribuem para a compreensão das trajetórias dos filhos de imigrantes e suas relações sociais e culturais. Dessa forma, é de suma importância a observação das relações que a língua e a cultura possuem na vida de um imigrante para que possamos compreender melhor o processo de imigração pelos olhos daqueles que o vivenciam.

The present study aims to analyze the role of Japanese as a heritage language in the context of Japanese immigration to Brazil. Through an extensive bibliographic review, the study seeks to discuss the history of Japanese immigration tied to the preservation of the Japanese language among the children of immigrants. With the arrival of the first Japanese immigrants in Brazil in the early 20th century, the Japanese language began to be transmitted to the immigrants' children as a cultural heritage. Divided between a family context and a society with distinct languages, the children and grandchildren of Japanese immigrants experienced varied interactions with the Japanese language, resulting in diverse experiences of being the child of a migrant. Beyond the individuals' identity traits, the Japanese language is observed to play a central role in the establishment of cultural associations that served as spaces for reterritorialization within the Brazilian environment by Japanese immigrants. These dynamics inherent to the migratory movement contribute to understanding the trajectories of immigrants' descendants and their social and cultural relationships. These dynamics inherent to the migratory movement contribute to understanding the trajectories of the children of immigrants and their social and cultural relationships. Therefore, it is extremely important to observe the relationships that language and culture have in the life of an immigrant so that we can better understand the immigration process through the eyes of those who experience it.
Analysis and discussions on Japanese as a heritage language in the Brazilian immigration context
Keywords: Imigração japonesa; Preservação cultural; Transmissão linguística; Identidade cultural; Reterritorialização; Associações culturais; Japanese immigration; Cultural preservation; Linguistic transmission; Cultural identity; Reterritorialization; Cultural associations